An Experimental Analysis of Grinding Parameters and Conditions on Surface Roughness of Finished Product. Issue 1 (1st July 2022) - Biswas, P; Bardhan, P K; Sarkar, A; Islam, M R; Mondal, D; Bag, S; Bose, S
Abstract: Higher grade or smooth surface finish mechanical components and mating parts with close limits and tolerances is one of the most important requirement of modern manufacturing industry. Grinding is the most dominating process among various manufacturing finish processes over final products that require in-depth investigation on how material removal processes influence the surface roughness of the finished products. In this work, an experimental analysis was carried out to evaluate the influence of various machining parameters and conditions on surface roughness of the final substrates. The main objective of this experimental work is to study the comparison of the effects of tools and conditions which are abrasive nature between Mild Steel (MS) and EN24 steel surface by using Depth of Cut (DOC).